ANALYSIS OF FACTORS AFFECTING THE RETURN ON ASSETS OF BANK LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2008-2011 - Wito Wito (Universitas Trisakti, 2014)
This research aims to analyze the influence of the non-performing loan, loan to deposit ratio, operational efficiency ratio, capital adequacy ratio and firm size on return on assets banking company listed on the Indonesia stock exchange during the period 2008-2011.The Sample used in this study is as much as 23 companies, whereas the methods of analysis used is multiple regression based on ordinary least square (OLS)The results showed that based on the test-t, it can be inferred that the non-performing loan, the operational efficiency ratio and firm size effect significantly to profitability (as measured by return on assets). While the loan to deposit ratio and capital adequacy ratio was not significant effect of the return on asset banking company. In the meantime, based on test-F all independent variables influence significantly to return on asset banking company listed on the Indonesia stock exchange period 2008-2011